2022
DOI: 10.1002/adfm.202210614
|View full text |Cite
|
Sign up to set email alerts
|

3D‐Printed Photoresponsive Liquid Crystal Elastomer Composites for Free‐Form Actuation

Abstract: Direct ink writing of liquid crystal elastomers (LCEs) offers a new opportunity to program geometries for a wide variety of shape transformation modes toward applications such as soft robotics. So far, most 3D-printed LCEs are thermally actuated. Herein, a 3D-printable photoresponsive gold nanorod (AuNR)/LCE composite ink is developed, allowing for photothermal actuation of the 3D-printed structures with AuNR as low as 0.1 wt.%. It is shown that the printed filament has a superior photothermal response with 27… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
31
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 62 publications
(36 citation statements)
references
References 53 publications
0
31
0
Order By: Relevance
“…Combined with inductive coupling WPT technology, LCE-based soft actuators are free from the constraints of wires and batteries, providing a safe and effective strategy for related applications that typically require remote actuation in enclosed and confined spaces. For further applications, we consider to use 4D printing technology to achieve more complicated deformation of untethered electrothermal LCE-based soft actuators. , Moreover, the geometry of the excitation coil should be further optimized to achieve uniform distribution of magnetic field, thereby enhancing the controllability and actuation stability of soft actuators. , In the future research, it is highly promising to directly detect the resistance of the closed LM circuit and transmit the data wirelessly to an external observation device through Bluetooth. In addition, it is also important to investigate how the resistance changes of electrothermal soft actuators will affect the Joule heating and the electrothermal performance.…”
Section: Discussionmentioning
confidence: 99%
“…Combined with inductive coupling WPT technology, LCE-based soft actuators are free from the constraints of wires and batteries, providing a safe and effective strategy for related applications that typically require remote actuation in enclosed and confined spaces. For further applications, we consider to use 4D printing technology to achieve more complicated deformation of untethered electrothermal LCE-based soft actuators. , Moreover, the geometry of the excitation coil should be further optimized to achieve uniform distribution of magnetic field, thereby enhancing the controllability and actuation stability of soft actuators. , In the future research, it is highly promising to directly detect the resistance of the closed LM circuit and transmit the data wirelessly to an external observation device through Bluetooth. In addition, it is also important to investigate how the resistance changes of electrothermal soft actuators will affect the Joule heating and the electrothermal performance.…”
Section: Discussionmentioning
confidence: 99%
“…The design of functional active open surfaces represents an opportunity to make strides in this area. Advanced open surface platforms: Although many open solid and liquid surfaces have been reported as functional platforms for droplet reactors, [ 131,198,211–213 ] the development of advanced open surface platforms with muti‐functional characteristics, such as active open surfaces for different chemical feeding rates, still needs consideration. Application area: Recent studies have reported that droplet reactors on open surfaces can be used in bioanalysis, [ 214 ] drug release, [ 215 ] pollutant removal, [ 216 ] and 3D printing. [ 217 ] Despite extensive progress, the application area of droplet reactors on open surfaces should be further investigated, with emphasis on high temperature reactions, [ 19 ] catalysis, [ 48 ] novel material synthesis, [ 48 ] and other areas.…”
Section: Discussionmentioning
confidence: 99%
“…Plasmonic nanoparticles, carbon nanomaterials, and organic photothermal agents have been incorporated into the matrices of shape-memory polymers, liquid crystals, hydrogels, , elastomers, , and biopolymers , to form photothermal actuators and robots. The photothermal conversion by light-absorbing materials leads to basic mechanical deformations, such as bending, twisting, rotating, and jumping, of thermally responsive components to function as grippers, mills, swimmers, and syringes. ,, Light-absorbing materials also serve as thermally responsive components in some actuators. Several metrics, including the generated stress and strain, Young’s modulus, durability, response time, and energy consumption, have been taken into account during the design of photothermal actuators and robots. Two types of Au nanocrystals, nanospheres and nanorods have been selectively dispersed into thermoplastic polyurethane shape-memory polymer films with a transition temperature of 55 °C (Figure a) .…”
Section: Applicationsmentioning
confidence: 99%